The evolving relation between earnings, dividends, and stock repurchases - Skinner, Douglas J. (Journal of Financial Economics, 2008)
This paper examines how the relation between earnings and payout policy has evolved over the last three decades. Three principal groups of payers have emerged: firms that pay dividends and make regular repurchases, firms that make regular repurchases, and firms that make occasional repurchases. Firms that only pay dividends are largely extinct. Repurchases are increasingly used in place of dividends, even for firms that continue to pay dividends. While other factors help explain the timing of repurchases, the overall level of repurchases is fundamentally determined by earnings. The results suggest that repurchases are now the dominant form of payout.